Hospice and palliative care in China: Development and challenges - Yuhan Lu; Youhui Gu; Wenhua Yu (Elsevier, 2018)
Hospice and palliative care have been demonstrated to improve quality of life, shorten hospital stays, and save costs. As a developing country, faced with a rapidly aging population and an increasing number of patients with life-threatening illnesses such as cancer, China has made great progress in promoting hospice and palliative care during the past few decades. A trained nurse can play a significant role in promoting quality hospice and palliative care by providing care, coordinating a multidisciplinary team, calling for policy support, and raising public awareness. It is critical for nurses to clearly understand the development and challenges that currently exist in the country. With this awareness, nurses will improve their ability to recognize and address patients' and families' needs, resulting in quality, dignified, and individualized end-of-life care.